Changes related to fatigue in cardiorespiratory response sensitivity to hypoxic and hypercapnic stimulation during strenuous physical load - Mishchenko, V.; Suchanowski, A.; Lysenko, O. (Baltic Journal of Health and Physical Activity, 2009)
Background: The aim was to study changes in the sensitivity of CRS responses of skilled athletes caused by fatigue during a strenuous physical load.